Tetracyclic Endiandric Acids Isolated from Endiandra kingiana Gamble (Lauraceae) with In vitro and Molecular Docking Studies of β-Glucuronidase Activity (Early view) - Nurul Najihah Husna Tanazi, Ahmad Nazif Aziz, M. Iqbal Choudhary, Sadia Siddiq, Muhamad Aqmal Othman, Mohammad Tasyriq Che Omar, Cécile Apel; Mohamad Nurul Azmi (Tropical Life Sciences Research, 2026)
β-Glucuronidase is a lysosomal enzyme that hydrolyses of glucuronide conjugates, playing a significant role in drug and xenobiotic metabolism as well as various disease processes. Elevated activity of this enzyme reactivates glucuronidated carcinogens, promoting tumorigenesis and inflammation. Thus, inhibiting β-glucuronidase has emerged as a promising therapeutic strategy, particularly for the prevention of colonic carcinogenesis. In this study, three endiandric acid derivatives named kingianic acid A (1), tsangibeilin B (2), and endiandric acid M (3) that isolated from Endiandra kingiana bark, were evaluated for their β-glucuronidase inhibitory activity. Their chemical structures were identified using spectroscopic data and by comparison with published reports. In vitro enzyme inhibition assays revealed that compound 2 (IC50 value of 7.5 ± 2.77 µM) exhibited the most potent inhibition compared to compound 1 (IC50 value of 292 ± 5.40 µM) and the positive control, D-saccharic acid-1,4-lactone (IC50 value of 45.75 ± 2.16 µM). In addition, molecular docking studies further supported these findings, demonstrating that compound 2 exhibited stronger binding affinity to β-glucuronidase (-9.9 ± 0.1 kcal/mol) than compound 1 (IC50 value of 292 ± 5.40 µM) and D-saccharic acid-1,4-lactone (-7.0 ± 0.1 kcal/mol). These results highlight the potential of compound 2 as a lead scaffold for the development of β-glucuronidase inhibitors and contribute to the growing interest in plant-derived compounds for therapeutic applications.